Design and simulation of a polarization‐insensitive metamaterial terahertz absorber with five bands. Issue 8 (15th April 2020) - Jia, Wei; Bai, Jing; Roberts, Kevin; Le, Khai Q.; Zhou, Debao
Abstract: In this work, a terahertz metamaterial absorber with five absorption bands that can be used in the areas of sensing, imaging, and detecting is investigated. The absorber structure contains four quarter‐sectional circular rings and a cross in a square ring layer, a dielectric layer, and ground metal layer. Simulation results display that the absorber with such configuration possesses five distinct high absorption peaks at 0.7, 1.6, 2.32, 2.63, and 3.15 THz and show polarization‐insensitive property due to its 4‐fold symmetric property. The physical origins of the absorber characteristics are attributed to dipolar and hexapolar resonances of the patterned metallic arrays on the top layer, as established by analyzing the electrical field density. In addition to, structural parameters' influences on the absorption bands are also studied and the results indicate that total absorption bands and coefficients can be effectively altered by changing the structural parameters and configurations, which is beneficial for its practical applications.